Kajian Beban Harian pada Jaringan Distribusi Penyulang Jelutung - Sabila, Rani; Djufri, Umar; Dewi, Rozlinda (Journal of Electrical Power Control and Automation (JEPCA), 2024)
A distribution network is a conveyor network that connects the load center substation with the customer. The distribution network functions to distribute electrical energy to customers according to the power and voltage needed. The distribution network line from the Aurduri GI Transformer Bay goes to the incoming to be lowered voltage from 150kv to 20kv. After the voltage is lowered, it is directly channeled to the Jelutung Feeder to find out the daily load on the distribution network. The population in this study is "Study of Daily Burden on the Distribution Network of Jelutung Feeders". The highest daily load is the electrical load that occurs at the highest time in 24 hours. This can be affected by household, industrial, commercial activities and weather conditions. Daily peak loads occur at certain times such as the afternoon. The lowest daily load usually occurs in the morning around 06.00 to 07.30. Average lowest current (I) R,S,T 92,275A and lowest power (P) 3.29Mw. While the average highest current is 212.7A and the highest power is 7.54Mw. The highest current in September was on the 15th with a power of 8.0 mw at 18.30.